Black Silicon Fabricated By Aluminium-Assisted Chemical Etching For Solar Cells - Uddin, Shahnawaz (2023)
In this research, aluminium (Al) catalyst is used to fabricate nanoporous black silicon (b-Si) via a newly developed process, called aluminium-assisted chemical etching (AACE). Al as catalyst having a low diffusivity (0.94 cm2/s) slows down the etching rate in the AACE process for a better control over the morphology of nanopores and makes the AACE process low-cost too.